APPLICATION OF ELECTRICAL RESISTIVITY TOMOGRAPHY TECHNIQUE FOR INVESTIGATION OF LANDSLIDES: A CASE FROM TURKEY - Drahor M.G.; Kurtulmuş T.Ö.; Göktürkler G.; Berge M.A. (My University, 2006)
Electrical resistivity imaging is a widely used tool in near surface geophysical surveys for investigation of various geological, environmental and engineering problems including landslide. In this study, an electrical resistivity tomography (ERT) survey was conducted in a landslide area, located in the Söke district of Aydin, Turkey. In 2003, the Neogene-aged units on the slope next to a newly built school building became unstable due to an excavation work and moved after a heavy rainfall. The resulting landslide partly covered the school. The authors carried out a 2-D resistivity survey along three profiles over the landslide mass using a Wenner configuration. It yielded useful information about the geometry and characteristics of the landslide. In addition, a 2-D synthetic resistivity modelling study was carried out to understand the response of the resistivity method to a landslide problem before the field surveys. Eight boreholes were also drilled in the landslide area. Both the drilling and resistivity results indicated the presence of a fault in the site. Also, the resistivity data from the line measured along the axis of the landslide revealed the surface of rupture. © Springer-Verlag 2006.
Keywords: ELECTRICAL RESISTIVITY TOMOGRAPHY; LANDSLIDE; SöKE; TURKEY; Кайнозой::Неоген; Cenozoic::Neogene